PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PERBUATAN SUMBANG (INCEST) DALAM KONSEP KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) BARU - Mahadhitya Putra, Nyoman; Sutara Djaya, I Wayan (Kertha Wicara : Journal Ilmu Hukum, 2013)
Incest is one of the criminal perpetration which regulated in article 294paragraph (1) of the Indonesian Criminal Code. However, this regulation still limited tothe requirement that the incestuous relationship is done with his biological childrenwho are not old enough. Whereas, incest itself contains a broad sense, so that on theIndonesian Criminal Code Bill, criminalizing incest to be one attention through theestablishment of new regulations on this matter. Such changes certainly would inflict ofchange also in determining of criminal responsibility against the offender.
Keywords: Incest, Criminal Responsibility, Criminal Code Bill